2012
DOI: 10.1098/rsob.120066
|View full text |Cite
|
Sign up to set email alerts
|

Cancer drug pan-resistance: pumps, cancer stem cells, quiescence, epithelial to mesenchymal transition, blocked cell death pathways, persisters or what?

Abstract: Although chemotherapy of tumours has scored successes, drug resistance remains the major cause of death of cancer patients. Initial treatment often leaves residual disease, from which the tumour regrows. Eventually, most tumours become resistant to all available chemotherapy. I call this pan-resistance to distinguish it from multi-drug resistance, usually describing resistance caused by upregulation of drug transporters, such as P-glycoprotein. In this review, I discuss mechanisms proposed to explain both resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 88 publications
(131 reference statements)
2
134
0
Order By: Relevance
“…In this study, cellular and molecular pharmacological data demonstrate that DLC-carborane compounds target cancer and primary GBM CSCs highly selectively and also that these agents exert a very significant pharmacological behavior while sparing normal cells. Based on the principle of the elimination of CSCs toward achieving patient long-term cure rates in the clinical setting [3,6,7], it is of significance that DLCcarborane compounds exert such remarkable effect on GBM CSC lines. The effect is most meaningfully demonstrated by the determined IC 50 values, which are markedly 18 lower than those calculated for normal cells (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, cellular and molecular pharmacological data demonstrate that DLC-carborane compounds target cancer and primary GBM CSCs highly selectively and also that these agents exert a very significant pharmacological behavior while sparing normal cells. Based on the principle of the elimination of CSCs toward achieving patient long-term cure rates in the clinical setting [3,6,7], it is of significance that DLCcarborane compounds exert such remarkable effect on GBM CSC lines. The effect is most meaningfully demonstrated by the determined IC 50 values, which are markedly 18 lower than those calculated for normal cells (ca.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that as long as technological advancements empower the translational medicine capacity in enabling the pharmacological exploitation of cancer cell molecular and genomic knowledge, the advances to therapeutically overcome heterogeneity and to target the tumor cell microenvironment will occur at increasing rates [2][3][4][5][6][7][8][9][10]. A major milestone towards organelle-specific drug delivery was reached by the discovery of delocalized lipophilic cations (DLCs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in melanoma research and drug development, 10-20% of clinically disease-free patients relapse 5-10 years following an initial treatment [1,2]. This phenomenon, which is known as tumor dormancy [3], has been related to the existence of therapy-resistant cells with stem-like activity [4][5][6]. Recent findings suggest that cancer stem cells, in response to chemotherapy, enter protective, prolonged, but reversible, quiescence [7] and remain dormant without causing any clinical manifestations until activated [8].…”
Section: Introductionmentioning
confidence: 99%
“…A major clinical problem in cancer therapy is resistance of tumors to all available therapies, a phenomenon called panresistance (1). After an initial response primary tumors and especially metastases do not respond anymore to treatment, including radiotherapy.…”
Section: Introductionmentioning
confidence: 99%